\(\sqrt{7}\) = ( \(\sqrt{7}-1\)...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a) Ta có: \(VT=8-2\sqrt{7}\)

\(=7-2\cdot\sqrt{7}\cdot1+1\)

\(=\left(\sqrt{7}-1\right)^2\)

=VP(đpcm)

b) Ta có: \(VT=\sqrt{8-2\sqrt{7}}-\sqrt{8+2\sqrt{7}}\)

\(=\sqrt{7-2\cdot\sqrt{7}\cdot1+1}-\sqrt{7+2\cdot\sqrt{7}\cdot1+1}\)

\(=\sqrt{\left(\sqrt{7}-1\right)^2}-\sqrt{\left(\sqrt{7}+1\right)^2}\)

\(=\left|\sqrt{7}-1\right|-\left|\sqrt{7}+1\right|\)

\(=\sqrt{7}-1-\left(\sqrt{7}+1\right)\)

\(=\sqrt{7}-1-\sqrt{7}-1=-2=VP\)(đpcm)

a) Ta có: \(VP=\left(3+\sqrt{6}\right)^2\)

\(=3^2+2\cdot3\cdot\sqrt{6}+\left(\sqrt{6}\right)^2\)

\(=9+6\sqrt{6}+6\)

\(=15+6\sqrt{6}\)≠VP

=> Sai đề rồi bạn